Degradês de conectividade: infraestrutura de internet e desigualdades territoriais da midiatização - Fanfa, Mauricio de Souza (2023)
The infrastructure of the Internet is the theme of this thesis. We highlight its social aspects, especially the characteristics and inequalities of its infrastructure as a conditioning factor of the mediatization process. The research problem is exposed in the following question: how are spacialities and media infrastructures related when taken as elements that express and reinforce inequalities and colonialities? The thesis aims to generally track agents and gather data and issues related to spaciality and Internet infrastructure. Specific objectives begin with the purpose of articulating knowledge capable of updating and problematizing the generalization of Internet connection and the debate on digital inclusion. Another specific objective is to question the common notion that the Internet is ubiquitous and problematize its universalizing claim. The empirical object of study is defined by the Internet infrastructure. Empirically, we work with data from multiple sources about connectivity and Internet access in Brazil. The thesis justifies itself by considering that the Internet constitutes an environment of proven potential for development, at the same time demonstrates ambiguities. Its expansive relationship with society should be nuanced and criticized. We also aim to make considerations that serve for the instruction and qualification of the posture of entities, technology criticism, private sector oversight, Internet governance, public policies, digital inclusion actions, and education and awareness. We seek to define our thesis through the following statement: the Internet infrastructure is conditioned by territorial, political, technical-scientific, and market issues. As a producer of a non-innovative landscape of territorial differences, the material expansion of the Internet is motivated by underlying interests that articulate themselves far beyond opportunity and demand and as a result of the modernity/coloniality relation. We present indexes and maps developed and analyzed that refer to the Brazilian Internet infrastructure. The history and management of the submarine cables that connect Brazil are also analyzed. Methodologically, this is a study of media infrastructure aligned with critical studies in Innovation Diffusion. Infrastructure studies have a multi-methodological sensitivity derived from Science, Technology, and Society studies (STS). Thus, we dialogue with aspects of ActorNetwork Theory and material semiotics. We combine this perspective with aspects of public policy analysis and document analysis. The maps and indexes developed consider data such as download rates, availability of broadband, among others. Connectivity data of the Brazilian regions and municipalities are compared, showing distinctions between adjacent and remote, urban and rural cities and regions. We identify and comment on the large advancement in Internet infrastructure recorded in the Midwest Region and the Amazon agricultural frontier between 2020-2022. From these observations, aspects of digital exclusion, colonialism, mediatization, globalization, modernization, territorial identities or the history of communications are discussed.